Extended Factors for Theory of Planned Behavior on Organic Food Consumption: A Review - Oky Primaroni; Tiara Septirosya (EKONOMIKA SYARIAH : Journal of Economic Studies, 2024)
Damage to land caused by conventional farming, as a result of the use of synthetic fertilizers and pesticides, threatens future food availability. Organic farming is considered one of the efforts to implement sustainable agriculture. Consumer preferences need to be directed towards consuming organic agricultural products, but there are still many other factors influencing this behavior. Numerous studies have been conducted to assess consumer behavior. Some of these studies use the Theory of Planned Behavior (TPB) model to determine whether or not a specific behavior is performed. The Theory of Planned Behavior (TPB) model still needs to be integrated with other factors that also influence the adoption of a particular behavior. This study aims to propose an alternative model based on the Theory of Planned Behavior (TPB) to understand consumer behavioral intentions regarding the consumption of organic food. A descriptive method with a systematic review approach was used in this study based on a review of articles related to consumer behavior in the organic food domain. An alternative model of the Theory of Planned Behavior (TPB), with several additional influencing factors such as Religiosity, Health Consciousness, Environmental Consciousness, Price Barrier, Trust, Availability, and Knowledge, is provided as input for researchers, practitioners, and policy makers.